DIRECTIONS AND MECHANISMS FOR THE IMPLEMENTATION OF THE DIGITAL AGENDA OF THE EAEU IN THE REPUBLIC OF BELARUS - P. A. Lis; V. I. Slizh; V. A. Bogush (Цифровая трансформация)
The article is devoted to the formation and implementation of the digital agenda of the Eurasian Economic Union. It describes the nature of the digital agenda, its objectives and strategies. The effectiveness of the implementation of the digital agenda of the EAEU, predicted by the specialists of the World Bank and the Eurasian Economic Commission, is considered. The characteristics of the starting conditions for the economic development of the EAEU member states at the time of the formation of the digital agenda is given. The analysis of the relative weight of Internet users, the readiness index for the electronic government and its components, as well as the coefficients of variation of these indicators is carried out. Based on this analysis, the place of the Republicof Belarusin the regional processes of the digital transformation of the economy and the reduction of the digital divide between the EAEU countries in 2006-2016 were identified. The analysis also led to identification of problems in the field of digital transformation of the economy, facing the EAEU countries, and possible ways of their solution.